Dari Regulasi Menuju Kesadaran: Pengaruh Penghapusan Batas Waktu PPh Final UMKM terhadap Manajemen Kepatuhan Pajak dan Kepatuhan Sukarela Wajib Pajak di Kota Pekanbaru - Erna Murniati; Natasha Nadira Putri; Torik Tri Putra; Muhammad Zahran Sulthon; Dwi Fionasari (GLOBAL SCIENTS PUBLISHER, 2026)
Government Regulation Number 20 of 2026 removed the time limit on the use of the 0.5% Final Income Tax (PPh Final) rate for individual taxpayers and sole proprietorships (Perseroan Perorangan), raising questions about the policy's impact on the compliance behavior of MSME operators. This study aims to analyze the effect of the policy removing the MSME Final Income Tax time limit on Tax Compliance Management and Voluntary Taxpayer Compliance among MSME operators in Pekanbaru City. The study employs a quantitative approach using a survey method involving 100 respondents selected via purposive sampling from a population of 27,358 MSME operators in Pekanbaru City. Data were analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach with SmartPLS 4 software. The results indicate that the policy removing the MSME Final Income Tax time limit has a positive and significant effect on both Tax Compliance Management (path coefficient 0.803; T-statistic 17.952; p 0.000) and Voluntary Taxpayer Compliance (path coefficient 0.710; T-statistic 10.212; p 0.000); thus, both research hypotheses (H1 and H2) are accepted. These findings indicate that the legal certainty provided by the policy encourages MSME operators to be more disciplined in managing tax administration while simultaneously increasing their awareness of fulfilling tax obligations voluntarily. This study is expected to serve as a basis for government evaluation in formulating more adaptive tax policies for MSMEs.